Utility of cardiac imaging in diagnosis of atypical presentation of cardiac fibroma. Issue 9 (5th September 2019) - Flores, Catalina; Lundberg, Jaclyn; Richardson, Randy R; Prasad, Deepa
Abstract : Primary cardiac tumours are relatively rare in the paediatric population, with benign tumours accounting for >90% of cases. Cardiac fibromas are rare primary tumours that typically reside in the ventricles. Symptoms are usually the result of blood outflow obstruction or disruption of the cardiac conduction system. They do not typically regress and usually require surgical intervention. In this case, we report a rare finding of a right atrial fibroma in an 18-month-old female who presented with lethargy and vomiting. Chest X-ray revealed an enlarged cardiac silhouette, and follow-up CT showed a 3.7×3.2×3.7 cm hypodense lesion in the right atrium. Cardiac MRI revealed the diagnosis, which was confirmed on pathology.